Doing social network research : network-based research design for social scientists - Robins, Garry (Los Angeles : Sage Publications Ltd, 2015)
'With straightforward guidance on research design and data collection, as well as social network analysis, this book takes you start-to-finish through the whole process of doing network research.'--Back cover.
The difference with social network research -- Fundamental network concepts and ideas -- Thinking about networks: Research quesstions and study design -- Social systems and data structures: Relational ties and actor attributes -- Network observation and measurment -- The empirical context of network data collection -- Ethical issues for social network research -- Network visualization: What it can and cannot do -- A review of social network analytic methods -- Drawing conclusions: Inference, generalization, causality and other weighty matters.
Includes bibliographic references (pages 231-254) and index.
Keywords: Social networks -- Research -- Methodology; Social sciences -- Network analysis